Operation and maintenance of air conditioning system for high rise building in Kuala Lumpur / Amnorshakirah Amir - Amir, Amnorshakirah (2007)
The air-conditioning system is important for all building especially for high-rise building. It is because the high-rise building not using the natural ventilation. Air conditioning system is the facilities for comfort and convenience for the occupant. Beside that, it used for protection of electrics equipment such as the control room in that building. Today, many types of air conditioning system that applies in high rise building. However, several of technology that adapt in the building for example for the new high rise building. The technology of aif conditioning system provided with the controller system for example the Building Automation System (BAS), Integrated Building Management System (IBMS) and etc. This Is providing ib fluency the operation and maintenance of air conditioning system in that building. The intention of this research is to study the air conditioning system in high rise building in Kuala Lumpur. The selected building for this research for air conditioning system at Menara Merais, Dataran Maybank and Menara Telekom. The aim of this research is to know the new technology Used of air conditioning included the maintenance of the system. Besides that, we want to know the efficient and effective less of the system used in tiie building. The hew technology system will be compared to older system and definite the advantages and disadvantages of the system.